Prognostic Value of CONUT and PNI on Hemoglobin and Clinical Outcomes of Chronic Kidney Disease Patients: A Systematic Review - Galaxy Gen Mahananda Putra Anang; Arfiyanti Arfiyanti; Arif Rachman (Bajang Institute, 2026)
Malnutrition and chronic inflammation are prevalent complications in chronic kidney disease (CKD) that contribute to disease progression and high mortality rates. The Controlling Nutritional Status (CONUT) score and Prognostic Nutritional Index (PNI) are objective immunonutritional tools, yet their comparative prognostic value and specific relationship with hemoglobin decline in CKD patients require comprehensive evaluation. This study aims to systematically analyze the prognostic accuracy of CONUT and PNI scores in predicting clinical outcomes and their correlation with hemoglobin levels in CKD patients. A systematic literature review was conducted via PubMed and Google Scholar for primary cohort studies published between 2023 and 2026. Six studies meeting the inclusion criteria were analyzed qualitatively. The findings demonstrated that high CONUT and low PNI scores were significantly associated with lower hemoglobin levels and a higher risk of malnutrition in CKD patients. Both indices independently predicted adverse clinical outcomes, including renal progression and mortality. PNI consistently showed robust predictive capacity for mortality, while composite scores effectively stratified risk in dialysis populations. In conclusion, the CONUT score and PNI are reliable and cost-effective predictors of adverse clinical outcomes and hemoglobin decline in CKD patients. Routine immunonutritional screening using these indices is essential to optimize clinical management